The impact of internationalization policies on Chinese State-owned Enterprises performance: A case study of Jianhuai Automobile (JAC) in Anhui province of China. - Attia, Mohamed (Advances in Social Sciences Research Journal, 2016)
The importance of SOEs performance in economic development cannot be overemphasized. The role of SOEs is assumed to be the key element of the Chinese economic performance. Recently Chinese economic development is on its booming stage and in this era of development SOEs consider being key partner. However, the earlier studies done on Chinese organizations were mostly aimed to highlight the SOEs financial performance, only few of them focused on government support and reforms towards SOEs. The Aim of this study was to utilize the framework of various prospects, for instance internationalization strategy, government support, outward foreign direct investment and strategic alliance etc. This study comprised on the brief and comprehensive case study of Anhui JiangHuai Automobile (JAC) in Hefei, Anhui province. The result from this study clearly indicates that by defining the contributing factors for the SOEs development in China, which enables the government to improve the performance of SOEs and give the best policies and future prospective reforms